Dielectric properties of the Maillard reaction solution formed between enzymatic hydrolysate of Antarctic krill and glucose under microwave heating. (1st May 2022) - Xu, Yongyang; Xiang, Ping; Qiu, Weiqiang; Feng, Yuhui; Jin, Yingshan; Deng, Shanggui; Tao, Ningping; Jin, Yinzhe
Abstract: A coaxial probe method has been used to measure the dielectric properties of the enzymatic hydrolysate and glucose Maillard reaction solution (MRS) of Antarctic krill under microwave heating and the penetration depth determined. The changes in pH, color, absorbance, amino acid content, and energy barrier of the MRS were investigated. The results show that the dielectric constant of the MRS decreased and the dielectric loss increased with an increase in the heating time in the frequency range of 300–3000 MHz ( p  < 0.05). Upon increasing the heating time, the penetration depth and pH gradually decrease. The color difference (△E) of the MRS increased as the heating time increased. The color values of the MRS are correlated with the dielectric constant and dielectric loss (R 2  > 0.93). Non-fluorescent intermediates and melanin are gradually accumulated as the heating time increased. During the progress of the Maillard reaction, the total amino acid content in the enzymatic hydrolysate decreased from 29.84 ± 0.23 to 16.56 ± 0.19 mg/mL, and the aliphatic amino acid content decreased the most. Under microwave heating conditions, the energy barrier required by the MRS was 7.0 (±0.01) × 10 −20 J. Highlights: The Maillard reaction can be described by dielectric properties. The color values of the MRS are correlated with the dielectric properties. During Maillard reaction, aliphatic amino acid content decreased most. The energy barrier required by the MRS was 7.0 (±0.01) × 10 −20 J. It provided a new approach to understand the Maillard reaction.